Efeito do treinamento multicomponente sobre o controle postural dinâmico de atletas amadores de basquetebol universitário - Lopes, Edson Gomes (2018)
Dynamic postural control (DPC) during basketball pull-up jump shot (PJS) movement depends on the strength of the core and custom with the natural situations of the game. A training method that spans both physical and technical-tactical training sessions (multi-component training - MCT) can be an effective tool to improve performance. It is not clear, however, to what extent the MCT can favor DPC. So, the purpose of this study is to investigate the effect of MCT on DPC on athletes of a male amateur basketball team during the PJS movement. The sample consisted of nine male amateur male basketball players (age: 23.3 ± 2.9 years, height: 181.5 ± 7.7 cm, body mass: 76.4 ± 5.0 kg). The athletes were evaluated before and after a 12-week period of MCT contemplating physical preparation (functional training) associated to technical-tactical training (small-sided games). Training sessions took place twice a week with a duration of 90 min. For the PJS assessment, each athlete started the zig-zag speed dribble movement, around cones located equidistantly (5.5 m), then performing the PJS. The entire procedure was filmed for later scanning of the images by a specific software for determination of the displacement of the center of gravity (CG). Data were analyzed by descriptive statistics, paired t-test, Cohen’s effect size, Pearson's correlation and magnitude based inference analysis (ɑ = 0.05). The reduction of CG displacement (19.4 ± 13.5 cm vs. 13.8 ± 12.6 cm, pre- and post-intervention, respectively, p = 0.08) and the final GC acceleration (0.96 ± 1.53 m/s2 vs. -0.56 ± 1.04 m/s2, pre and post-intervention, respectively, p = 0.06) bordered the level of significance. There was no difference in the initial (12.4 ± 14.8 J vs. 8.8 ± 9.54 J, pre- and post-intervention, respectively, p = 0.76) and final kinetic energy values (13.1 ± 15.7 J vs. 6.6 ± 8.64 J, pre- and post-intervention, respectively, p = 0.86). Magnitude based inference analysis indicated that MCT was probably beneficial for reducing GC displacement on the anteroposterior axis and for final kinetic energy. It is concluded that the MCT is able to reduce the variation of the CG displacement in the anteroposterior axis during PJS, indicating a higher DPC in university basketball amateur athletes.